ISOLASI DAN IDENTIFIKASI SENYAWA FLAVONOID FRAKSI ETIL ASETAT EKSTRAK DAUN AFRIKA (Vernonia amygdalina Del.) - Ni Ketut Esati; I Putu Eka Budiarta; Kadek Duwi Cahyadi; Gusti Ayu Dewi Lestari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
African leaves (Vernonia amygdalina Del.) are reported to have activity as anti-malarial, antibacterial, anticancer, antioxidant, and others. This is closely related to the secondary metabolite compounds, that are contained in african leaves. One of the secondary metabolites that have a big role in the efficacy of african leaves is flavonoids. So that the purpose of this study, to isolated and identified the flavonoid compounds from african leaves. The plants were picked directly in the Tabanan area, Bali. The stages of this study were making the ethanol extract of african leaves, skrinning of the secondary metabolite compounds from the ethanol extract of african leaves. After that, the isolation and purification of flavonoids in ethyl acetate fraction from extract of african leaves are doing. Then the isolate of flavonoid compounds are identified using Ultra Violet-Visible (UV-Vis) and Infrared (IR) spectrophotometer methods. From the results of this study, the yield of ethanol extract was 3.693% derived from maceration of African leaf simplicia powder using 96% ethanol as solvent. The results of phytochemical screening, African leaf ethanol extract contains alkaloids, flavonoids, phenolic compounds, steroids, and saponins. The results of the fractionation obtained n-hexane fraction as much as 2.57 grams, ethyl acetate fraction 0.53 grams, and water fraction as much as 3.02 grams. The flavonoid compounds in the ethyl acetate fraction were separated and isolated, resulting in 2 isolates which were further identified by UV-Vis and IR spectrophotometry. The results obtained with the addition of shear reagents that the ethyl acetate fraction contains flavonoids of the flavone group (7-hydroxyl free), and on examination by IR spectrophotometry showed the presence of OH groups, aliphatic CH, C=O, aromatic C=C, CO alcohol, and aromatic CH.